Foundation history of the first bacteriological institute in Siberia (on the occasion of centenary of the foundation of Ivan and Zinaida Churiny Bacteriological Institute) - E. M. Kharitonova; A. G. Tolopilo (Бюллетень сибирской медицины)
In this article there is presented the information about the first Siberian Bacteriological Institute, it history, role and traditions. Names and biographies of the creators of this medical institution are given.